ANALISIS PENGARUH DISTRIBUTIVE JUSTICE DAN PROCEDURAL JUSTICE TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN ETHICAL BEHAVIOR SEBAGAI VARIABEL MEDIASI DAN ORGANIZATIONAL CULTURE SEBAGAI VARIABEL MODERASI - Mardiyanti, Ira; Suharnomo, Suharnomo (Faculty of Economics and Business Diponegoro University, 2017)
Human resource is the most important factor for creating excellence that can not be easily duplicated by competitors and specific to each organization. Work behaviors such as organizational citizen behavior (OCB) receive more attention because they contribute effectively within the organization. Managers can create employees have the organizational citizen behavior (OCB) by treating them respectfully and fairly, help it consider individual needs, and provide a supportive working environment. The purpose of this study is to describe and analyze further on the analysis of the influence of distributive justice and procedural justice on organizational citizenship behavior with ethical behavior as mediating variables and organizational culture as a moderating variable. This study differs from studies that have been there since they rarely research using variables mediating and moderating variables simultaneously by connecting five are planned.The data in this study were collected through questionnaires and implemented to 94 permanent employees of PT Telekomunikasi Indonesia (TELKOM) Tbk. Regional Division IV Central Java and Yogyakarta region that are not at the managerial level and has a service life of more than one year based on the method of random sampling with lottery technique. Mechanical testing of the data used in this study include test reliability, validity, classical assumptions, path analysis, Sobel test to test the effect of mediation, and moderation test using five models in the regression model.The results of this study indicate that the distributive justice influential imply a positive and significant impact on ethical behavior, procedural justice influential in a positive and significant impact on ethical behavior, distributive justice affect positively and significantly on Organizational Citizenship Behavior (OCB), procedural justice affect positively and significantly to Organizational Citizenship behavior (OCB), and ethical behavior influence positively and significantly mediate on Organizational Citizenship behavior (OCB). Distributive justice proved to be positive and significantly moderate the organizational culture and ethical conduct, procedural justice proved positive and significantly moderate the organizational culture and ethical behavior, distributive justice does not influence positively and significantly moderate the organizational culture and Organizational Citizenship Behavior (OCB), procedural justice proved positively and significantly moderate the organizational culture and organizational Citizenship behavior (OCB), and ethical behavior proved to be positive and significantly moderate the organizational culture and organizational Citizenship behavior (OCB).